Valuing personal effort as a method for achieving academic success (Journal of Parents and Teachers, 2026)
A team of psychologists and teachers at the centre has implemented a system that allows personal effort to be observed and evaluated as a key tool against academic failure. We will be able to observe various habits of organisation, attention and participation in the classroom so that they can be included in the final grade to encourage better behaviour.
Keywords: Effort; Motivation; Academic failure; Learning; Habits; Assessment